Method for evaluating storage performance of graphite, graphite and application of graphite
By defining the specific surface area, Id/Ig value, particle size, and orientation degree of graphite as indicators P1, the problem of the inability to evaluate the storage performance of graphite in the existing technology is solved, thereby improving the storage performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202410558671.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2025-11-07
AI Technical Summary
Existing technologies cannot effectively evaluate the storage performance of graphite, which prevents the storage performance of lithium-ion batteries from being improved.
The specific surface area, Id/Ig value, particle size, and orientation degree of negative electrode sheet of graphite are defined as P1, and their range is limited to 0.0001 to 0.36. The storage performance of graphite is evaluated by the formula P1=B*I*(Dv5-Dv0)/Dv50/OI.
By using the defined index P1, graphite with good storage performance can be screened out, thereby improving the storage performance of lithium-ion batteries.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of secondary batteries, in particular to a method for evaluating storage performance of graphite, graphite with excellent storage performance and application thereof. BACKGROUND
[0002] The storage performance of lithium ion batteries is one of the indicators of the batteries, and in the field of power batteries, the storage performance is one of the core items for evaluation and improvement. Graphite, as the only or main constituent of the negative electrode material, its type will seriously affect the storage performance of lithium ion batteries. Various indicators of graphite, such as specific surface area, Id / Ig value, OI value and particle size, will have different effects on storage. However, there is currently no technology directly connecting the various indicators of graphite with the storage performance, so it is difficult to evaluate the storage performance of graphite.
[0003] Therefore, it is necessary to define an indicator to evaluate the storage performance of graphite, so as to screen out graphite with good storage performance and ultimately improve the storage performance of lithium ion batteries. SUMMARY
[0004] Therefore, it is necessary to define an indicator to evaluate the storage performance of graphite, so as to screen out graphite with good storage performance and ultimately improve the storage performance of lithium ion batteries.
[0005] Another object of the present application is to provide a method for evaluating the storage performance of graphite.
[0006] Another object of the present application is to provide a negative electrode material.
[0007] Another object of the present application is to provide a negative electrode.
[0008] Another object of the present application is to provide an electrochemical device.
[0009] Another object of the present application is to provide a vehicle.
[0010] To achieve the above objects, the first aspect of the present application provides a graphite, which satisfies:
[0011] P1=B*I*(Dv5-Dv0) / Dv50 / OI;
[0012] wherein P1 is the storage performance of the graphite; B is the specific surface area of the graphite, in m2 / g; I is the Id / Ig value of the graphite; Dv5 is the particle size of the graphite, in μm; Dv0 is the particle size of the graphite, in μm; Dv50 is the particle size of the graphite, in μm; and OI is the OI value of the negative electrode tab made of the graphite. 2 / g; I is a peak intensity ratio Id / Ig of D peak and G peak in a Raman spectrum of the graphite; Dv0, Dv5 and Dv50 are particle size values corresponding to 0%, 5%, 50% of cumulative volume distribution percentage of the graphite, and units are all μm; OI is an orientation degree of the negative electrode sheet made of the graphite;
[0013] 0.0001≤P1≤0.36.
[0014] In some embodiments, the B is 0.8 m 2 / g to 3 m 2 / g.
[0015] In some embodiments, the I is 0.1 to 1.
[0016] In some embodiments, the OI is 5 to 40.
[0017] In some embodiments, the Dv0 is >1 μm and the Dv5-Dv0 is 1 μm to 3 μm.
[0018] In some embodiments, the Dv50 is 5 μm to 20 μm.
[0019] In some embodiments, the P1 is 0.0001 to 0.06.
[0020] A second aspect of the present application provides a method for evaluating storage performance of graphite, comprising:
[0021] defining an index P1 representing the storage performance of the graphite, so that the P1 satisfies: P1=B*I*(Dv5-Dv0) / Dv50 / OI, wherein B is a specific surface area of the graphite, unit is m 2 / g; I is a peak intensity ratio Id / Ig of D peak and G peak in a Raman spectrum of the graphite; Dv0, Dv5 and Dv50 are particle size values corresponding to 0%, 5%, 50% of cumulative volume distribution percentage of the graphite, and units are all μm; OI is an orientation degree of the negative electrode sheet made of the graphite;
[0022] obtaining the B, the I, the Dv0, the Dv5, the Dv50 and the OI, and generating a value of the P1 based on the B, the I, the Dv0, the Dv5, the Dv50 and the OI;
[0023] judging whether the value of the P1 satisfies a preset value;
[0024] if the value of the P1 satisfies the preset value, judging that the storage performance of the graphite is good;
[0025] If the value of P1 does not satisfy the preset value, it is determined that the storage performance of the graphite is poor.
[0026] In some embodiments, the preset value is a, 0.0001≤a≤0.36.
[0027] In some embodiments, when the value of P1 satisfies the preset value, the smaller the value of P1, the better the storage performance of the graphite.
[0028] In some embodiments, when the value of P1 satisfies the first preset value, the method further comprises:
[0029] determining whether the value of P1 satisfies a second preset value;
[0030] If the value of P1 satisfies the second preset value, it is determined that the storage performance of the graphite is excellent.
[0031] If the value of P1 does not satisfy the second preset value, it is determined that the storage performance of the graphite is good.
[0032] In some embodiments, the second preset value is b, 0.0001≤b<0.06.
[0033] A third aspect of the present application provides a negative electrode material, comprising the graphite described in the present application.
[0034] A fourth aspect of the present application provides a negative electrode, comprising the negative electrode material described in the present application.
[0035] A fifth aspect of the present application provides an electrochemical device, comprising the negative electrode described in the present application.
[0036] A sixth aspect of the present application provides a vehicle, comprising the electrochemical device described in the present application.
[0037] The graphite described in the present application can at least bring the following beneficial effects:
[0038] The index P1 integrating the specific surface area, Id / Ig value, particle size of the graphite and the OI value of the negative electrode tab made of the graphite is defined for evaluating the storage performance, and is limited in the range of 0.0001 to 0.36, so as to ensure that the screened graphite has good storage performance.
[0039] Additional aspects and advantages of the present application will be in part apparent and in part pointed out hereinafter. DETAILED DESCRIPTION
[0041] In the present application, the disclosure of numerical ranges includes all values and further subdivisions of the ranges within the entire range, including the endpoints and subranges given for the ranges.
[0042] In the present application, the raw materials, equipment, etc. involved, unless otherwise specified, are raw materials, equipment that can be made by commercial means or known methods; the methods involved, unless otherwise specified, are conventional methods.
[0043] The graphite of the embodiments of the present application satisfies the following conditions:
[0044] P1 = B * I * (Dv5-Dv0) / Dv50 / OI
[0045] Wherein, P1 is the storage performance of the graphite; B is the specific surface area of the graphite, in units of m 2 / g; I is the peak intensity ratio Id / Ig of the D peak and the G peak in the Raman spectrum of the graphite; Dv0, Dv5 and Dv50 are the particle size values corresponding to the cumulative volume distribution percentages of the graphite reaching 0%, 5% and 50%, respectively, all in units of μm; OI is the orientation degree of the negative electrode sheet made of the graphite; 0.0001≤P1≤0.36.
[0046] It should be noted that in the embodiments of the present application, Id refers to the amorphous carbon content, in units of cm -1 ; Ig refers to the graphitized carbon content, in units of cm -1 . The Id and Ig values can be read from the peak height of the Raman graph, Id ranges from 1000-1500 cm -1 , and the value of the highest peak is read; Ig ranges from 1500-1800 cm -1 , and the value of the highest peak is read.
[0047] As an optional example, the test method of I is shown in Table 1.
[0048] Table 1 Test method of I
[0049]
[0050] In some embodiments, I is 0.1 to 1, including but not limited to 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc. In the embodiments of the present application, the larger I is, the greater the proportion of amorphous carbon is, and the active sites of amorphous carbon are more than those of graphitized carbon, and the Li +The more, the faster the capacity attenuation, and the worse the storage performance. In the embodiments of the present application, I is 0.1-1, which can balance the storage and fast charging performance. The fast charging performance is highly related to the content of amorphous carbon. The greater the content, the higher the reaction activity, the better the fast charging performance, but the worse the storage performance, so a balance between the two needs to be sought. Less than 0.1 indicates that the proportion of amorphous carbon is too low, and the fast charging performance of graphite is extremely poor. Greater than 1 indicates that the proportion of amorphous carbon is too large. The active sites of amorphous carbon are more than those of graphitized carbon, and more Li + The more, the faster the capacity attenuation, and the worse the storage performance.
[0051] In the embodiments of the present application, OI, also referred to as OI value, can be tested by X-ray diffractometer (XRD). OI = I(004) / I(110), I(004) and I(110) correspond to the peak height of 54.3° and 77.5° respectively. The greater the OI, the more obvious the anisotropy, and the more Li + The insertion rate is slower, and the side reaction is less, which is beneficial to the storage performance.
[0052] In some embodiments, OI is 5-40, including but not limited to 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39 or 40, etc. In the embodiments of the present application, OI is 5-40, which can achieve a balance between storage and fast charging. Less than 5, the anisotropy is not obvious, and the Li + The insertion rate is fast, and the side reaction is more, which is not conducive to improving the storage performance. Greater than 40, the proportion of amorphous carbon is too low, the storage performance is good, but the fast charging performance is poor.
[0053] In the embodiments of the present application, the greater the specific surface area (B), the more the reaction sites, and the more the consumed Li + The more, the faster the capacity attenuation, and the worse the storage performance.
[0054] In some embodiments, B is 0.8 m 2 / g to 3 m 2 / g, including but not limited to 0.8 m 2 / g, 1.0 m 2 / g, 1.5 m 2 / g, 2.0 m 2 / g, 2.5 m 2 / g, or 3 m 2 / g, etc. In the embodiments of the present application, B is 0.8 m 2 / g to 3 m 2 / g, the reaction site is moderate, the reaction site is moderate, and the balance of storage and fast charging can be achieved; less than 0.8 m 2 / g, the graphite particles are too large, the lithium ion insertion and extraction rate is slow, and the fast charging performance is not good; greater than 3, the graphite particles are small, the surface active site is more, the reaction rate is fast, which is beneficial to fast charging but not to storage.
[0055] The particle size refers to the size of the particles. According to the volume distribution, the particle size range is Dv0-Dv100. In the embodiments of the present application, Dv0, Dv5 and Dv50 need to be focused on in terms of storage. Since the numerical range of Dv0 and Dv50 partially overlaps, Dv5-Dv0 is used to represent the fine powder in this part, and Dv0 is required to be greater than 1 μm and the range of Dv5-Dv0 is 1 μm to 3 μm; (Dv5-Dv0) / Dv50 represents the proportion of fine powder of the particles. The more fine powder will cause too many side reactions, which will further deteriorate the storage.
[0056] As a non-limiting enumeration, the value of Dv5-Dv0 includes but is not limited to 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, etc.
[0057] In some embodiments, Dv50 is 5 μm to 20 μm, including but not limited to 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm, etc.
[0058] In some embodiments, P1 includes but is not limited to 0.0001, 0.0005, 0.0015, 0.002, 0.0030, 0.04, 0.05, 0.06, 0.07, 0.1, 0.15, 0.2, 0.25, 0.3 or 0.36, etc. In the embodiments of the present application, P1 is 0.0001 to 0.36, the graphite has good storage performance, and the smaller P1 is within this range, the better the storage performance of the graphite is. The mechanism involved may be: the larger B represents the more reaction sites, the more Li + consumed, the faster the capacity decay, and the worse the storage performance; the larger I represents the larger the proportion of amorphous carbon, the more active sites of amorphous carbon than the active sites of carbon after graphitization, the more Li + consumed, the faster the capacity decay, and the worse the storage performance; (Dv5-Dv0) / Dv50 represents the proportion of fine powder, and the more fine powder will deteriorate the storage performance due to too many side reactions; the larger OI represents the more obvious anisotropy, the slower the Li + insertion rate, fewer side reactions, and better storage performance.
[0059] P1 is less than 0.0001, although the smaller P1 is, the better the storage is, but the faster charging performance is worse, so when P1 is less than 0.0001, the faster charging performance is deteriorated; greater than 0.36, it is possible that the specific surface area is too large, I is too large, the proportion of fine powder is too large, and the OI value is too small, at least one of the four reasons, leading to the deterioration of the storage performance of the graphite.
[0060] As an optional example, 0.0001≤P1<0.06, at this time, the graphite can be considered as the preferred graphite with excellent storage performance.
[0061] The graphite of the embodiments of the present application can at least bring the following beneficial effects:
[0062] The specific surface area, Id / Ig value, particle size of the graphite, and the OI value of the negative electrode tab made of the graphite are integrated to define the index P1 for evaluating the storage performance, and P1 is limited to be within the range of 0.0001 to 0.36, so as to ensure that the screened graphite has good storage performance.
[0063] The method for evaluating the storage performance of the graphite according to the embodiments of the present application comprises the following steps:
[0064] S101, defining an index P1 representing the storage performance of the graphite, so that P1 satisfies: P1=B*I*(Dv5-Dv0) / Dv50 / OI, wherein B is the specific surface area of the graphite, the unit is m 2 / g; I is the peak intensity ratio Id / Ig of the D peak and the G peak in the Raman spectrum of the graphite; Dv0, Dv5 and Dv50 are particle size values corresponding to the cumulative volume distribution percentage of the graphite reaching 0%, 5% and 50% respectively, and the units are μm; OI is the orientation degree of the negative electrode tab made of the graphite.
[0065] In the embodiments of the present application, the explanations of the parameters B, I, Dv0, Dv5, Dv50 and OI in step S101 are the same as the foregoing graphite of the embodiments of the present application, which will not be repeated here.
[0066] S102, obtaining B, I, Dv0, Dv5, Dv50 and OI, and generating the value of P1 based on B, I, Dv0, Dv5, Dv50 and OI.
[0067] It should be noted that "generating the value of P1 based on B, I, Dv0, Dv5, Dv50 and OI" in step S102 can be understood as bringing the values of B, I, Dv0, Dv5, Dv50 and OI into P1=B*I*(Dv5-Dv0) / Dv50 / OI to calculate the value of P1.
[0068] S103, determining whether the value of P1 meets the first preset value; if the first value of P1 meets the preset value, it is determined that the storage performance of the graphite is good; if the value of P1 does not meet the first preset value, it is determined that the storage performance of the graphite is poor.
[0069] In some embodiments, the first preset value is a, and 0.0001≤a≤0.36.
[0070] As a non-limiting enumeration, a includes but is not limited to 0.0001, 0.0005, 0.0015, 0.002, 0.0030, 0.04, 0.05, 0.06, 0.07, 0.1, 0.15, 0.2, 0.25, 0.3 or 0.36, etc.
[0071] In some embodiments, when the value of P1 meets the above-mentioned first preset value, the smaller the value of P1, the better the storage performance of the graphite.
[0072] In some embodiments, when the value of P1 meets the above-mentioned first preset value, the method for evaluating the storage performance of the graphite according to the embodiments of the present application further comprises:
[0073] determining whether the value of P1 meets the second preset value;
[0074] if the value of P1 meets the second preset value, it is determined that the storage performance of the graphite is excellent;
[0075] if the value of P1 does not meet the second preset value, it is determined that the storage performance of the graphite is good.
[0076] In some embodiments, the second preset value is b, and 0.0001≤b<0.06.
[0077] As a non-limiting enumeration, b includes but is not limited to 0.0001, 0.0002, 0.0005, 0.0015, 0.002, 0.0030, 0.04, 0.05 or 0.059, etc.
[0078] The negative electrode material according to the embodiments of the present application comprises the graphite according to the embodiments of the present application.
[0079] In some embodiments, the negative electrode material comprises at least one of a negative electrode active material, a negative electrode conductive agent, a negative electrode binder, and the like, wherein the negative electrode active material comprises the graphite of the embodiments of the present application. It should be noted that in the embodiments of the present application, the specific selection of the negative electrode conductive agent, the negative electrode binder, and the like is not particularly limited. As a non-limiting enumeration, the negative electrode conductive agent comprises, but is not limited to, at least one of carbon nanotubes, conductive carbon black, conductive graphite, vapor-grown carbon fibers, graphene, and the like; the negative electrode binder comprises, but is not limited to, at least one of carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), and the like. The negative electrode active material can be solely the graphite of the embodiments of the present application, or can be composed of the graphite of the embodiments of the present application and other components, and the specific selection of the other components is not particularly limited, for example, can be at least one of mesocarbon microbead (MCMB), soft carbon, hard carbon, elemental silicon, SiO, silicon-carbon composite material (SiNPs-amorphous carbon, SiNPs-graphite, and the like), or metal oxide material (TiO2-B, MoO, CoO, and the like), and the like.
[0080] The negative electrode of the embodiments of the present application comprises the negative electrode material of the embodiments of the present application.
[0081] In some embodiments, the above-mentioned negative electrode further comprises a negative electrode current collector and a negative electrode material layer formed on the negative electrode current collector, wherein the negative electrode material layer comprises the negative electrode material of the embodiments of the present application.
[0082] In some embodiments, the negative electrode current collector can be selected to comprise copper or any other suitable conductive metal foil (such as solid or mesh or clad foil), metal grid or mesh, or porous metal known to those skilled in the art. In certain variants, the surface of the negative electrode current collector can comprise a metal foil that has been surface treated (e.g., carbon coated and / or etched).
[0083] The electrochemical device of the embodiments of the present application comprises the negative electrode of the embodiments of the present application.
[0084] In some embodiments, the above-mentioned electrochemical device comprises, but is not limited to, a secondary battery such as a lithium ion battery, a capacitor, and the like. Among them, the secondary battery is not limited to one of a button cell, a soft pack battery, a large battery (for example, a square battery and a cylindrical battery, and the like), and the like.
[0085] In some embodiments, the above-mentioned electrochemical device further comprises a positive electrode, and the positive electrode comprises a positive electrode material, and the positive electrode material comprises at least one of a positive electrode active material, a positive electrode conductive agent, a positive electrode binder, and the like. In the embodiments of the present application, the specific selection of the positive electrode active material, the positive electrode conductive agent, the positive electrode binder, and the like is not particularly limited. As a non-limiting enumeration, the positive electrode active material comprises, but is not limited to, at least one of lithium iron phosphate, lithium cobaltate, lithium manganate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, fluorinated lithium vanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, ternary positive electrode material (NCM, NCA), and the like; the positive electrode conductive agent comprises, but is not limited to, at least one of carbon black, acetylene black, graphene, carbon fiber, C60, carbon nanotube, and the like; and the positive electrode binder comprises, but is not limited to, at least one of polyvinylidene fluoride (PVDF), sodium alginate, sodium carboxymethyl cellulose, and polyacrylic acid.
[0086] In some embodiments, the positive electrode further comprises a positive electrode current collector, and the positive electrode current collector can be selected to comprise aluminum or any other suitable conductive metal foil (such as solid or mesh or clad foil), metal grid or mesh, or porous metal known to those skilled in the art. In certain variations, the surface of the positive electrode current collector can comprise a metal foil that is surface treated (e.g., carbon coated and / or etched).
[0087] In some embodiments, the above-mentioned electrochemical device further comprises a separator, and the separator is arranged between the positive electrode and the negative electrode.
[0088] In some embodiments, the separator comprises, but is not limited to, at least one of polyethylene (PE), polypropylene (PP), polyolefin (PO) separator mainly comprising polytetrafluoroethylene, polyester film (such as polyethylene terephthalate (PET) film), cellulose film, polyimide film (PI), polyamide film (PA), spandex or aramid film, woven film, non-woven film (non-woven fabric), microporous film, composite film, separator paper, calendered film, or spunlaced film, and the like.
[0089] It should be noted that in the embodiments of the present application, the thickness and the like of the above-mentioned positive electrode, negative electrode, and separator are not limited, as long as the purpose of the present application can be achieved.
[0090] The preparation method of the electrochemical device of the embodiments of the present application is not limited, and can be any method known to those skilled in the art.
[0091] The vehicle of the embodiments of the present application comprises the electrochemical device of the embodiments of the present application.
[0092] As a non-limiting enumeration, the above-mentioned vehicle comprises, but is not limited to, a car, a motorcycle, a power-assisted bicycle, a bicycle, a power tool, and the like.
[0093] The negative electrode material, the negative electrode, the electrochemical device and the vehicle provided by the embodiments of the present application have at least the beneficial effects of the graphite provided by the embodiments of the present application.
[0094] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0095] I. Test methods of various indexes of graphite in each embodiment and comparative example
[0096] The test method of specific surface area (B) is as follows: a dynamic method is used for testing. The dynamic method is that the sample to be tested is loaded in a U-shaped sample tube, a mixed gas containing a certain proportion of adsorbate flows through the sample, and the adsorption amount of the sample to be tested on the adsorbate molecules (N2) is determined according to the change of gas concentration before and after adsorption. After the adsorption amount of the adsorbate gas is determined, the specific surface of the powder to be tested can be calculated from the adsorption amount of the adsorbate molecules.
[0097] The test method of Id / Ig (I) is as follows: the Raman spectrum of the graphite is tested by a laser microscopic confocal Raman spectrometer (Horiba, LabRAM HR Evolution), and the laser wavelength of the Raman spectrometer can be in the range of 532nm to 785nm. The graphite powder is taken for testing, and a range of 100μm×100μm is scanned for testing the particles in the range, 40*40=1600 points are tested at equal intervals, and the test range of each point is between 0.305cm -1 and 0.805cm -1 . The peak appearing between 1000cm -1 and 1500cm -1 is a d peak, and the peak appearing between 1500cm -1 and 1800cm -1 is a g peak. The values of the highest peaks of the d peak and the g peak are read as Id and Ig respectively, the intensity ratio of Id / Ig of each point is counted, and the average value of 1600 points is calculated as the final intensity ratio of Id / Ig.
[0098] The test method of particle size is as follows: the graphite powder is pre-dispersed in alcohol, added to the equipment, and the built-in ultrasonic is started for 1min for testing.
[0099] The test method of the orientation degree (OI) is as follows: graphite, Super-P, binder CMC and binder PVDF are mixed in a mass ratio of 96:1:1:2 (the weight of graphite is 10 g), 20 g of water is added to prepare a slurry, the slurry is ultrasonically treated for 20 min and then placed on a magnetic stirrer for stirring for 10 min at a stirring rate of 500 r / min; then the slurry is taken out and uniformly and evenly coated on a 12 μm copper foil by using a fixed-thickness (such as 250 μm, 500 μm, etc., preferably 250 μm) doctor blade. The copper foil is placed in a 80 °C air-drying oven for 2 h, the foil is taken out, cut into a circular pole piece with a diameter of 14 mm, and placed in a 120 °C vacuum drying oven for drying for 5 h to obtain a pole piece. The pole piece is subjected to a pole piece level test, specifically, an X-ray diffractometer (XRD) test (Cu Kα target, 40 KV / 40 mA voltage and current) is performed, the peak height values of the 2θ angles of 54.3° and 77.5° are extracted, and the orientation degree OI value is obtained by dividing the peak height values.
[0100] II. Examples and Comparative Examples
[0101] Example 1
[0102] (Method for evaluating storage performance of graphite)
[0103] The method for evaluating the storage performance of graphite of the present embodiment, wherein the graphite is graphite of Model A, comprises the following steps:
[0104] (1) defining an index P1 representing the storage performance of the graphite, such that P1 satisfies: P1 = B*I*(Dv5-Dv0) / Dv50 / OI, wherein B is the specific surface area of the graphite, with a unit of m 2 / g; I is the peak intensity ratio Id / Ig of the D peak and the G peak in the Raman spectrum of the graphite; Dv0, Dv5 and Dv50 are the particle size values corresponding to the cumulative volume distribution percentages of 0%, 5% and 50% of the graphite, respectively, all with a unit of μm; and OI is the orientation degree of the negative pole piece prepared from the graphite.
[0105] (2) it is tested that B = 0.8 m 2 / g, I = 0.1, Dv5-Dv0 = 1 μm, Dv50 = 20 μm, and OI = 40, and then the values of B, I, Dv0, Dv5, Dv50 and OI are substituted into P1 = B*I*(Dv5-Dv0) / Dv50 / OI to calculate that P1 is 0.0001.
[0106] (3) determining whether P1 calculated in step (2) satisfies a first preset value a, wherein 0.0001≤a≤0.36.
[0107] (4) After judging that P1 calculated in step (2) satisfies the first preset value, it is judged that the graphite of the embodiment has good storage performance.
[0108] (5) Since P1 calculated in step (2) satisfies the first preset value, it is further judged whether P1 calculated in step (2) satisfies a second preset value b, 0.0001≤b<0.06.
[0109] (6) After judging that P1 calculated in step (2) does not satisfy the second preset value, it is judged that the graphite of the embodiment has good storage performance.
[0110] (Graphite)
[0111] The graphite of the embodiment has a model A, which satisfies the formula: P1=B*I*(Dv5-Dv0) / Dv50 / OI;
[0112] wherein, P1 is the storage performance of the graphite; B is the specific surface area of the graphite, with a unit of m 2 / g; I is the peak intensity ratio Id / Ig of the D peak and the G peak in the Raman spectrum of the graphite; Dv0, Dv5 and Dv50 are the particle size values corresponding to the cumulative volume distribution percentages of 0%, 5% and 50% of the graphite, respectively, with a unit of μm; and OI is the orientation degree of the negative electrode tab made of the graphite.
[0113] After testing, B=0.8m 2 / g, I=0.1, Dv5-Dv0=1μm, Dv50=20μm, and OI=40.
[0114] Substituting the values of B, I, Dv0, Dv5, Dv50 and OI into the above formula, P1 is calculated as 0.0001.
[0115] (Negative electrode)
[0116] The negative electrode of the embodiment comprises a negative electrode current collector and a negative electrode material layer arranged on the opposite two side surfaces of the negative electrode current collector, and the negative electrode current collector is a copper foil with a thickness of 12μm. The negative electrode material of the negative electrode material layer is composed of the following components in parts by weight: 96 parts of the graphite of the embodiment, 1 part of Super-P, 1 part of carboxymethyl cellulose (CMC), and 2 parts of polyvinylidene fluoride (PVDF).
[0117] (Preparation method of negative electrode)
[0118] The preparation method of the negative electrode of the present example is as follows: graphite of the present example, Super-P, CMC, and PVDF are mixed in a mass ratio of 96:1:1:2 (the weight of graphite is 10 g), 20 g of water is added to prepare a slurry, the slurry is ultrasonically treated for 20 min and then placed in a magnetic stirrer for stirring for 10 min at a stirring rate of 500 r / min; then the slurry is taken out and uniformly and evenly coated on a 12 μm copper foil using a scraper with a fixed thickness (such as 250 μm, 500 μm, etc., and 250 μm is recommended). The copper foil is placed in a 80℃ air drying oven for 2 h, the foil is taken out, cut into a circular electrode with a diameter of 14 mm, and placed in a 120℃ vacuum drying oven for drying for 5 h to obtain the negative electrode of the present example.
[0119] (electrochemical device)
[0120] The electrochemical device of the present example is a lithium ion battery, specifically a button cell, which comprises a positive electrode, a negative electrode, a separator, and an electrolyte.
[0121] The positive electrode comprises a positive electrode current collector and a positive electrode material layer provided on the opposite two sides of the positive electrode current collector, and the positive electrode current collector is an aluminum foil with a thickness of 12 μm. The positive electrode material of the positive electrode material layer is composed of the following components in parts by weight: NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2) 80 parts, Super-P 10 parts, and polyvinylidene fluoride (PVDF) 10 parts.
[0122] The negative electrode is the negative electrode of the present example.
[0123] The separator is provided between the positive electrode and the negative electrode, and the separator is a polypropylene separator with a thickness of 20 μm.
[0124] The electrolyte is a mixed solution of 1 mol / L LiPF6 in ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1.
[0125] (preparation method of electrochemical device)
[0126] The preparation method of the electrochemical device of the present example comprises the following steps:
[0127] (1) Positive electrode preparation: according to the weight ratio of NCM811, Super-P, and polyvinylidene fluoride (PVDF) of 80:10:10 (the weight of NCM811 is 10 g), 15 g of N-methyl-2-pyrrolidone (NMP) is added to make a uniform slurry, and the slurry is uniformly and evenly coated on an aluminum foil with a fixed thickness (such as 250 μm, 500 μm, etc., preferably 250 μm) doctor blade. The aluminum foil is placed in a 80°C air drying oven for 2h, then the foil is taken out, cut into a circular electrode with a diameter of 14mm, and placed in a 120°C vacuum drying oven for 5h to obtain a positive electrode.
[0128] (2) Assembly of electrochemical device: assemble the positive electrode shell, positive electrode, separator, negative electrode, foam nickel, and negative electrode shell in order, and drop in an appropriate amount of electrolyte during assembly to form a button cell.
[0129] Examples 2-6 and Comparative Examples 1-2 are basically the same as Example 1, except that the type of graphite and its corresponding parameter index, storage performance evaluation results are different, as shown in Table 2. In addition, in Examples 2-6 and Comparative Examples 1-2, their respective graphites are used for graphite storage performance evaluation, negative electrode preparation, electrochemical device preparation, etc.
[0130] Table 1 Part of graphite types and their parameter indexes, storage performance evaluation results of Examples 1-6 and Comparative Examples 1-2
[0131]
[0132] As can be seen from Table 1, the storage performance index P1 of the graphites A, B, C, D, E, F, G, and H corresponding to Examples 1-6 and Comparative Examples 1-2 increases in turn, so it can be predicted that the storage performance of the graphites A, B, C, D, E, F, G, and H decreases in turn. Among them, since the storage performance index P1 of the graphites corresponding to Examples 1-5 are all within the second preset value (0.0001≤b<0.06), it is judged that the storage performance of the graphites corresponding to Examples 1-5 is excellent. The storage performance index P1 of the graphite corresponding to Example 6 is within the first preset value (0.0001≤a≤0.36), but not within the second preset value (0.0001≤b<0.06), so it is judged that the storage performance of the graphite corresponding to Example 6 is good. Similarly, the storage performance index P1 of the graphites corresponding to Comparative Examples 1 and 2 are not within the first preset value (0.0001≤a≤0.36), so it is judged that the storage performance of the graphites corresponding to Comparative Examples 1 and 2 is poor.
[0133] Storage performance verification test:
[0134] The electrochemical devices of each example and comparative example were tested for 60°C storage for 30 days, and the specific test method was:
[0135] ①Capacity: The electrochemical device (i.e. button cell) of each example or comparative example was cycled at 0.33C (1C=190 mA / g), 2.5-4.25V for 3 cycles, and the discharge capacity of the third cycle was taken as the capacity of the electrochemical device C0.
[0136] ②Storage: The electrochemical device obtained in step ① was charged to 4.25V at constant current (CC) 0.33C0, constant voltage (CV) 0.05C0, and then the electrochemical device was placed in a constant temperature oven at 60℃ for 30 days.
[0137] ③After storage: After 30 days, the electrochemical device obtained in step ② was taken out, first discharged at constant current (DC) 0.33C0 to 2.5V, and the discharge capacity at this time was recorded as C1; then charged at constant current (CC) 0.33C0, constant voltage (CV) 0.05C0, and discharged at constant current (DC) 0.33C0 to 2.5V, and the discharge capacity at this time was recorded as C2. C1 was the retention capacity, and C2 was the recovery capacity. 100%*C1 / C0 was the capacity retention rate, and 100%*C2 / C0 was the capacity recovery rate.
[0138] The test results of the electrochemical device of each example and comparative example after 60℃ storage for 30 days are shown in Table 3.
[0139] Table 3 Test results of the electrochemical device of each example and comparative example after 60℃ storage for 30 days
[0140]
[0141] From Table 3, it can be seen that the smaller the P1, the higher the capacity retention rate and capacity recovery rate of the graphite, which is consistent with the performance initially predicted in Table 2, indicating that the method has high reliability.
[0142] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific feature, structure, material or characteristic described in connection with the embodiment or example is included in at least one embodiment or example of the present application. In the present specification, illustrative representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any appropriate manner in any one or more embodiments or examples. In addition, the person skilled in the art can combine and combine the different embodiments or examples described in the present specification and the features of the different embodiments or examples without contradiction.
[0143] In addition, the terms "first", "second", etc. are used only for the purpose of description, and should not be understood as indicating or implying relative importance or a specific number of the technical features indicated. Therefore, the features defined as "first", "second" can explicitly or implicitly include at least one of the features. In the description of the present application, the meaning of "a plurality of" is at least two, such as two, three, etc., unless otherwise explicitly and specifically limited.
[0144] Although the embodiments of the present application have been shown and described above, it is understood that the above-described embodiments are exemplary and should not be construed as limiting the present application, and those skilled in the art can make changes, modifications, replacements and variations to the above-described embodiments within the scope of the present application.
Claims
1. A graphite characterized by, The graphite satisfies: P1=B*I*(Dv5-Dv0) / Dv50 / OI; Wherein, P1 is the storage performance of the graphite; B is the specific surface area of the graphite, unit is m 2 / g; I is the peak intensity ratio Id / Ig of D peak and G peak in the Raman spectrum of the graphite; Dv0, Dv5 and Dv50 are the particle size values corresponding to the cumulative volume distribution percentages of 0%, 5% and 50% of the graphite, units are μm; OI is the orientation degree of the negative electrode sheet made of the graphite; 0.0001≤P1≤0.36。 2. The graphite according to claim 1, characterized in that, The B is 0.8 m 2 / g to 3 m 2 / g.
3. The graphite of claim 1, wherein The I is 0.1 to 1.
4. The graphite of claim 1, wherein The OI is 5 to 40.
5. The graphite of claim 1, wherein The Dv0 is greater than 1 μm and the Dv5-Dv0 is 1 μm to 3 μm; And / or, the Dv50 is 5 μm to 20 μm.
6. The graphite of claim 1, wherein The P1 is 0.0001 to 0.
06.
7. A method for evaluating the storage performance of graphite, characterized by The method comprises: An index P1 representing the storage performance of the graphite is defined, and the P1 satisfies: P1=B*I*(Dv5-Dv0) / Dv50 / OI, wherein B is the specific surface area of the graphite, and the unit is m2 / g; I is the peak intensity ratio Id / Ig of the D peak and the G peak in the Raman spectrum of the graphite; Dv0, Dv5 and Dv50 are particle size values corresponding to the cumulative volume distribution percentages of 0%, 5% and 50% of the graphite, and the units are μm; and OI is the orientation degree of the negative electrode tab made of the graphite. 2 / g; I is the peak intensity ratio Id / Ig of the D peak and the G peak in the Raman spectrum of the graphite; Dv0, Dv5 and Dv50 are particle size values corresponding to the cumulative volume distribution percentages of 0%, 5% and 50% of the graphite, and the units are μm; and OI is the orientation degree of the negative electrode tab made of the graphite. Obtaining the B, the I, the Dv0, the Dv5, the Dv50 and the OI, and generating a value of the P1 based on the B, the I, the Dv0, the Dv5, the Dv50 and the OI; Determining whether the value of the P1 satisfies a first preset value; If the value of the P1 satisfies the first preset value, determining that the storage performance of the graphite is good; If the value of the P1 does not satisfy the first preset value, determining that the storage performance of the graphite is poor.
8. The method of claim 7, wherein, The first preset value is a, 0.0001≤a≤0.36; And / or, when the value of the P1 satisfies the first preset value, the smaller the value of the P1, the better the storage performance of the graphite.
9. The method according to claim 7 or 8, characterized in that, When the value of the P1 satisfies the first preset value, the method further comprises: Determining whether the value of the P1 satisfies a second preset value; If the value of the P1 satisfies the second preset value, determining that the storage performance of the graphite is excellent; If the value of the P1 does not satisfy the second preset value, determining that the storage performance of the graphite is good.
10. The method of claim 9, wherein, The second preset value is b, 0.0001≤b<0.
06.
11. A negative electrode material, characterized in that, The graphite as claimed in any one of claims 1 to 6.
12. A negative electrode characterized by comprising: The negative electrode material as claimed in claim 11.
13. An electrochemical device, characterized by, The negative electrode as claimed in claim 12.
14. A vehicle characterized by comprising: The electrochemical device as claimed in claim 13.